Antiviral Activity of 3-Deazaguanine, 3-Deazaguanosine, and 3-Deazaguanylic Acid - Allen, Lois B. (1977)
3-Deazaguanine (ICN 4221), 3-deazaguanosine (ICN 4793), and 3-deazaguanylic acid (ICN 5412) represent a new class of synthetic guanine analogs having antiviral activity. In vitro, nine ribonucleic acid and seven deoxyribonucleic acid viruses were inhibited, including influenza, parainfluenza, rhino-, vesicular stomatitis, adeno-, herpes-, cytomegalo-, vaccinia, pseudorabies, and myxoma viruses. They were effective orally against influenza types A and B and parainfluenza type 1 (Sendai) virus infections in mice, with a therapeutic index of 16 against the latter two viruses. The course of herpes encephalitis was altered only when the drugs were applied directly into the brain. In addition, these drugs were effective inhibitors of Friend leukemia virus-induced splenomegaly in mice; treatment also produced extensions of life in these animals.